Comparing aboveground carbon stocks in coffee agroforestry and secondary and primary forests in Gayo Highlands, Indonesia - Anhar, Ashabul; Hayati, Durrah; Muslih, Ali M.; Siregar, Astri Winda; Jamilah, Maryam; Baihaqi, Akhmad; Muzaifa, Murna; Abubakar, Yusya; Hanan, A. (Frontiers in Forests and Global Change, 2025)
Tropical agroforestry systems can mitigate climate change through carbon storage while supporting biodiversity and improving livelihoods. This study evaluates the potential of coffee agroforestry systems in the Gayo Highlands, Indonesia, to achieve carbon storage levels comparable to secondary and primary forests. Vegetation data are collected across three locations, covering coffee agroforestry, secondary forest, and primary forest. We found that primary forests had the highest carbon stocks, with 223.53 tC ha−1 in Location 1, 194.68 tC ha−1 in Location 2, and 542.55 tC ha−1 in Location 3. Coffee agroforestry in Location 1 had carbon stocks comparable to secondary forest, while in Location 3, it showed the lowest carbon stock (6.26 tC ha−1). Higher carbon stocks were linked to greater tree species richness, larger DBH, and higher basal areas. Additionally, we observed a positive relationship between tree basal area and aboveground carbon stock, confirming that forests with higher basal area values exhibit greater carbon storage capacity. The findings underscore the critical role of mature trees in carbon storage and highlight the value of preserving mature forest species in coffee agroforestry systems.